Plyometric training: acquisition and maintenance of muscle power in senior men`s soccer players - Janeira, M. A.; Silva, J. A.; Faria, R. (2001)
The aims of this study were to: i) evaluate the effects of plyometric training in some indicators of muscular power in soccer players; ii) identify changes induced by plyometric training on the values of weight, muscular grith of the lower members and body fat from subcutaneous fat measurements and; iii) evaluate the effects of the absence of plyometric training on the test items previously identified. The sample was comprised of 20 senior soccer players from Madeira island, belonging to a 3rd league Portuguese Championship team. The experimental was conducted in two phases. Firstly, the athletes were trained for 8 weeks, with a bi-weekly frequency, to 2 programs of plyometric training [the first program (2 weeks). This program consisted of simple plyometric exercises. The second program (6 weeks) was composed mainly by deep jumps (DJ - 32 cms and 40 cms)]. On the second phase, the athletes were aleatory distributed in two groups, one reduced training group (RTG) which continued to be submitted to the second program of plyometrics, but training exclusively once a week; the other group, group in absence of training (GAT) did not go through any plyometric training. Power performance of the athletes was evaluated through squat and counter movement jumps (Bosco et al, 1983), a 20m speed test (Kollath et al., 1991; Marella et al., 1993) and a 4x5.50m shuttle-run (Neumaier, 1984). Somatic dimensions (weight, height, 4 skinfolds. and 2 girths) were assessed according to the procedures of Ross & Marfell-Jones (1991). Differences were analyzed using t-test, Mann-Wittney test and Wilcoxon test. For the first phase, statistically significant improvements were found for all muscle power indicators (p<0.05). On the other hand, no significant alterations were observed in the somatic dimensions (p>0.05). In the second phase of the study, the statistical similarity of the 2 sub-groups studied was evident (p>0.05). Conclusions: i) plyometric training revealed to be an effective training to improve muscle power; ii) plyometric training does not induce alterations on somatic dimensions, and iii) the reduction of plyometric training frequency and the absence of specific training do not lead to any significant changes of the effects previously induced on the selected variables.